Proximal Tibia Tumour Location and Curettage Are Major Risk Factors of Local Recurrence in Giant Cell Tumour of Bone - Mahdal, Michal; Tomáš, Tomáš; Apostolopoulos, Vasileios; Adámková Krákorová, Dagmar; Múdry, Peter; Staniczková Zambo, Iva; Pazourek, Lukáš (Cancers, 2023)
Giant cell tumour of bone (GCTB) is one of the most common local aggressive tumourous lesions with a wide variety of biological behaviour. However, there are no clear indicative criteria when choosing the type of procedure and the complication rates remain high, especially in terms of local recurrence. The purpose of the study was to (1) identify the main risk factors for local recurrence, (2) evaluate the recurrence-free survival in dependence on neoadjuvant denosumab use and the type of procedure, and (3) compare the functional outcomes after curettage and en bloc resection. The group included 102 patients with GCTB treated between 2006 and 2020. The mean age of patients was 34.4 years (15-79). The follow-up period was 8.32 years (2-16) on average. Local recurrence occurred in 14 patients (29.8%) who underwent curettage and in 5 patients (10.6%) after en bloc resection. Curettage was shown to be a factor in increasing recurrence rates (OR = 3.64 [95% CI: 1.19-11.15]; p = 0.023). Tibial location was an independent risk factor for local recurrence regardless of the type of surgery (OR = 3.22 [95% CI: 1.09-9.48]; p = 0.026). The recurrence-free survival rate of patients treated with resection and denosumab was higher compared to other treatments at five years postoperatively (p = 0.0307). Functional ability and pain as reported by patients at the latest follow-up were superior after curettage compared to resection for upper and lower extremity (mean difference: -4.00 [95% CI: -6.81 to -1.18]; p < 0.001 and mean difference: -5.36 [95% CI: -3.74 to -6.97]; p < 0.001, respectively). Proximal tibia tumour location and curettage were shown to be major risk factors for local recurrence in GCTB regardless of neoadjuvant denosumab treatment. The recurrence-free survival rate of patients treated with resection and denosumab was higher compared to other treatments. The functional outcome of patients after curettage was better compared to en bloc resection.